PERBANDINGAN KEPAILITAN ANTARA BADAN HUKUM (PERSEROAN TERBATAS) DENGAN NON BADAN HUKUM (FIRMA) - Hudyarto (The Juris, 2019)
This writing concerning the comparison of the system of business entity liability in the form of a Limited Liability Company legal entity with a non-legal entity business entity which is sentenced to a bankruptcy decision. With the decision of the Pilit statement to the extent of the responsibility of the board of directors, personally the directors, the board of commissioners and the personal board of commissioners. Likewise, the extent to which the responsibility for the Firm is sentenced to a decision on bankruptcy. The point here is that whether the directors must be responsible for the decision on bankruptcy statements where the directors have been careful, did not make mistakes, did not commit negligence and did not have personal interests, and carried out as outlined in the Articles of Association of the Limited Liability Company. Likewise for Firms that are sentenced to bankruptcy decisions, where firms do not have wealth that is separate from the wealth of the firm and the wealth of the firm's management. For this reason, I have conducted a study of Law No. 37 of 2004 concerning Bankruptcy Laws and Delays in Obligations of Debt Payments, Law Number 40 of 2007 concerning Limited Liability Companies, and Burgerlijk Wetboek (B.W.) or Civil Code.